Developing Critical Thinkers: Integrating Inquiry with BMKII in Scientific Writing - Harsono, Harsono; Suyitno, Imam; Harsiati, Titik; Andajani, Kusubakti (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research is significant because critical thinking and scientific writing abilities are crucial for student success. The study aims to investigate the impact of using BMKII instructional materials on students' critical thinking skills in scientific writing. The research methodology involves quantitative analysis (pretest and posttest) and qualitative methods (semi-structured interviews and reflective journals). Findings indicate a significant improvement in scientific writing skills post-intervention, with the average posttest score (78.72) significantly higher than the pretest score (53.36), supported by Paired Samples T-Test statistical analysis. Interviews and reflective journals provide insights into students' perceptions of the inquiry-based approach to scientific writing, a crucial stage in BMKII. Triangulation of quantitative and qualitative findings strengthens the conclusion regarding the effectiveness of BMKII. The study suggests practical implications for instructors and acknowledges limitations, such as instructor readiness and strategies for effective research-based learning implementation. Additionally, the article outlines the stages of critical thinking involved in scientific writing, emphasizing that each stage demonstrates critical thinking abilities. This research presents strong evidence that the use of BMKII contributes to enhancing students' critical thinking skills in scientific writing and preparing students to meet the demands of the 21st-century